You take a bath - I A Mason, David; Widdowson, Dan (Mankato, Minnesota Cantata Learning, 2016)
This fun and catchy song accompanied playful illustrations will help children learn why we keep our bodies clean. Germs, dirt, food spills, and more are no match for a bubbly bath!"--Publisher's description
Rhymes and Songs
a gift from book africa
1 2 13
Keywords: Baths -- Juvenile literature; Baths -- Health aspects -- Juvenile literature; Hygiene -- Juvenile literature